The role of criminal investigation unit in South Sulawesi regional police about law enforcement against makers and hoax information spreaders - Ismail Iskandar; Muhadar Muhadar; Hijrah Hijrah (Jurnal Cakrawala Hukum, 2021)
This study aims to determine the role of the criminal investigation unit in South Sulawesi Regional Police about law enforcement against hoax spreaders and to investigate crime prevention efforts by the criminal investigation unit in South Sulawesi Regional Police against perpetrators and hoaxes. This research is an empirical juridical study using interview and literature research methods as data collection techniques which are then analyzed qualitatively and presented descriptively. As for the conclusions of this study, viz. (1), the criminal investigation unit in South Sulawesi Regional Police plays a role in law enforcement against spreading hoax news crime, i.e. conducting investigations and investigations of special crimes, coordination, operational supervision, and administration of PPNS investigations in accordance with laws and regulations provisions. which is carried out based on the ideal role, the expected role, and the actual role, and (2) criminal investigation unit in South Sulawesi Regional Police in enforcing the law against the Crime of Information Dissemination or Hoax News conducts socialization efforts, broadcast public service advertisements and cyber patrols as a preventive or non-penal effort and conducts an investigation and investigation process based on the Criminal Procedure Code and Law Number 19 of 2016 concerning Information and Electronic Transactions (ITE) as a repressive or penal effort.How to cite item: Iskandar, I., Muhadar, M., Hijrah, H. (2021). The role of criminal investigation unit in South Sulawesi regional police about law enforcement against makers and hoax information spreaders. Jurnal Cakrawala Hukum, 12(3), 284-293. doi:https://doi.org/10.26905/idjch.v12i3.5159.